Pengembangan Sistem Peringatan Dini Masa Kontrak Kerja Karyawan dengan Menerapkan Pendekatan Kolaboratif Athena pada Elisitasi Kebutuhan (Studi Kasus PT. Surya Optima Nusa Raya) - Reza Fahrur Rasyid; Fajar Pradana; Bayu Priyambadha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Surya Optima Nusa Raya is a plastic Manufacturing Company. From the observations and discussions that have been conducted, found that the employees whose their contract have been expires can not confirm their attendance automatically on the attendance system that has existed in the company because the process of their extension contract has not been completed, and the agreements only occur by the mouth only, plus the attendance system considers that employees whose their contract expires has left the company without regard to the process of their extension contract has been completed or not. Early warning systems can be a solution for monitoring the contract and provide a warning. To do that, the system analyst must clarify the requirement by using some requirement analysis method in requirement engineering phase. One method that can be used to produce a more detailed requirements is to adopt a collaborative approach athena on requirements elicitation. Based on the results of the research, it can be concluded the process of requirements engineering software by applying a collaborative approach Athena successfully analyzed 24 system requirements from total of 26 requirements. Based on the results of measurement requirement metric, it can be concluded that the quality of document software requirements specification requirements that have been obtained by applying a collaborative approach athena has met some standard metrics that exist in the metric requirement